2011
DOI: 10.1007/s11908-011-0208-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Patients with Spinal Cord Injuries

Abstract: Spinal cord injuries (SCI) result in different lower urinary tract dysfunctions. Because of both the disease and the bladder drainage method, urinary tract infections (UTIs) are one of the most frequent conditions seen in SCI patients. Diagnosis is not always easy due to lack of symptoms. Asymptomatic bacteriuria needs no treatment. If symptoms occur, antibiotherapy is indicated. Duration depends mainly on severity of illness and upper urinary tract or prostatic involvement. Choice of antibiotherapy should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 50 publications
2
44
1
1
Order By: Relevance
“…High bladder pressure is a risk factor for renal failure and symptomatic UTI. 3,13 It promotes vesicoureteral reflux and ischemic injury to the bladder walls, creating favorable conditions for infection. 5 It is speculated that detrusor BoNTA injection induced inhibition of detrusor overactivity and decrease of detrusor pressure were responsible for the decrease of symptomatic UTI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High bladder pressure is a risk factor for renal failure and symptomatic UTI. 3,13 It promotes vesicoureteral reflux and ischemic injury to the bladder walls, creating favorable conditions for infection. 5 It is speculated that detrusor BoNTA injection induced inhibition of detrusor overactivity and decrease of detrusor pressure were responsible for the decrease of symptomatic UTI.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Neurogenic detrusor overactivity (NDO), elevated intravesical pressure, reflux, elevated post void residuals, commonly found in SCI population, increase the risk of UTI. 4,5 Detrusor botulinum toxin A (BoNTA) injection is an effective method to treat NDO and decrease detrusor pressure, [6][7][8][9] but whether this method can suppress UTI is still in dispute and there was rare report.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infection was found to occur in high rates in traumatic SCI. In another study, a frequency of 52.6% and 67.1% urinary tract infection has been reported in NT and traumatic SCI patients, respectively (14). New et al evaluated the complications of rehabilitation patients only in the non-traumatic SCI patients and found that urinary tract infection was the most common complication (45.7%) (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor in CAUTI is permanent low pressure voiding with permanent indwelling catheters or clean intermittent catheterization. 2 Regarding causative bacteria for CAUTI in spinal injury patients, Escherichia coli was the most common isolated pathogen (50%), followed by Pseudomonas aeruginosa (17.3%) and Enterococcus faecalis (7.7%). Recent antibiotic-resistant strains in UTI include multidrug resistant P. aeruginosa (MDRP), which is resistant to aminoglycosides, fluoroquinolones and beta-lactams.…”
Section: Introductionmentioning
confidence: 99%